Japan’s Foreign Policy Shifting in 2022 - Anisa, Khaira; Martínez, Juan Miguel Carboni (SOSHUM : Jurnal Sosial dan Humaniora, 2024)
This article examines Japan's significant foreign policy changes in 2022, focusing on three crucial documents: the National Security Strategy (NSS), the National Defence Strategy (NDS), and the Medium-Term Defence Force Buildup Program (MTDP), issued on December 6, 2022. The NSS, a pivotal strategic document, outlines Japan's foreign policy direction and includes plans to increase defence spending to 2% of GDP by 2027. It also introduces the concept of the Capability for Counterattacks, both of which signify a shift in Japan's approach to foreign policy. Japan's anti-militarism stance, rooted in Article 9 of its Constitution, prohibits the maintenance of military forces. This article aims to explore the factors driving Japan's foreign policy changes in 2022. Using a qualitative research methodology that incorporates both primary and secondary data sources, this study will analyze these factors through the lens of Coplin’s theoretical framework. According to Coplin’s Theory, changes in Japan’s foreign policy are influenced by three indicators: 1) Domestic politics, 2) Economic and military conditions, and 3) International context.